LAW ENFORCEMENT ON THE UTILIZATION OF STATE-OWNED ASSETS IN THE KEDUNGOMBO RESERVOIR REVIEWED FROM ARTICLE 167 OF THE CRIMINAL CODE - Krispriati, Desika Ratnaningtyas; Purnawan, Amin (Jurnal Hukum Khaira Ummah, 2023)
Kedungombo Reservoir as an asset of State property, experiencing problematic area management related to legal aspect. These problems include the uncontrolled number of floating net cages, land conversion, and unauthorized land grabs. This journal is based on the question of how 1) the system of preventing the use of state assets, 2) law enforcement in terms of Article 167 Paragraph (1) of the Criminal Code, and 3) what are the constraints and solutions to prevent the utilization of state assets by non- interested in the Kedungombo Reservoir of Central Java. The objective is to know and analyze 1) the system for preventing the use of state property assets; 2) law enforcement viewed from Article 167 Paragraph (1) of the Criminal Code and 3) obstacles and solutions to improve the prevention system of utilization of state property assets. The approach used is sociological juridical. The result of the research explains that the prevention system of the utilization of state-owned assets consists of input components, in the form of regulations related to the utilization of reservoirs, BBWS Pemali Juana, stakeholders and Local Government. The process, regulatory awareness efforts, community empowerment activities to strengthen aspects of community welfare. The output of the interdependence of roles between BBWS, the community and stakeholders in managing the reservoir for the sustainability of its resources is maintained. The main activities of active approach is to run the program of preventing the damage of natural resources and its infrastructure, as well as the socialization of the crime of natural resources in accordance with the laws and regulations. While the passive approach collects reports from the public associated with the destruction of natural resources and facilities. Law enforcement of the utilization of state property assets in the reservoir under article 167 of the Criminal Code includes reprimands and appeals, or the maximum form of making Statement by unauthorized parties. Obstacle prevention system utilization of State Property Assets in Reservoir is derived from water resources that experience sedimentation and behavior of the surrounding community who built illegal buildings and planting corn in Green Belt protected area and the use of floating net cages that exceed the limit. The solution is the application of environmentally friendly agriculture (terracing), maximizing the utilization of organic fertilizers and pesticides. In addition, fishery cultivation is limited. The surrounding community behavioral constraints are resolved with legal awareness and economic reinforcement through a non-penal approach by multiple stakeholders and defensive strategies.Keywords: Law enforcement, utilization of state property, article 167 of the Criminal Code.